Transmissão de política macroeconômica: o caso de Brasil e Alemanha - Führ, Janaína (2015)
This research studies the macroeconomic transmission of fiscal policy between Brazil and Germany in the period from the first month of 2001 to the twelfth month of 2013.The objective is to analyze the effects of long run transmission of Germany's fiscal policy on economic aggregates Brazilian: consumption, output, real money holdings, the terms of trade and domestic price, verifying if this effect is beggar-thy-neighbor, beggar-thyself or prosper-thy-neighbor. For this, we make an empirical application of the theoretical model of macroeconomic interdependence proposed by Corsetti and Pesenti (2001) applying the methodology of time series models Autoregressive Structural Vectors with exogenous variable - SVARX. The results from the SVARX and impulse response analysis indicate that the growth rate of consumption of domestic households is not affected by the German fiscal policy. However, the results for the long-term equation of domestic product, domestic real money balances, terms of trade and prices of household goods indicate that the German fiscal policy has beggar-thy-neighbor effect as indicated in the theoretical model of Corsetti and Pesenti (2001).